PENYERAPAN COBALT-60 DARI AIR OLEH TANAMAN KIAPU (Pistia stratiotes L.) - Safitri, Lailatul Nuzzulul; Tjahaja, Poppy Intan; Suryatika, Ida Bagus Made (BULETIN FISIKA, 2015)
Has conducted research Cobalt-60 radionuclide uptake by plants kiapu ( Pistia stratiotes L. ) found in many waters. The purpose of the study was to determine the value of the transfer factor on plant kiapu to Cobalt-60 in water. The study was conducted by growing plants on media kiapu gutter water in pots with the height 35 cm and diameter 11,5 cm containing Cobalt-60. The amount of Cobalt - 60 is absorbed and accumulated by the plant parts, i.e. roots and leaves, was observed by measuring the activity of Cobalt - 60 in the parts of the plant using a gamma spectrometer. Value of the transfer factor is determined by comparing the concentration of Cobalt-60 plants accumulated against its concentration in water. From this research, the highest transfer factor values obtained approximately 8000 ml/g in the roots. The value of the transfer factor of more than 1 ml/gr indicates that kiapu is a plant that has the ability to accumulate radionuclides Cobalt-60. Keywords : absorption, Cobalt-60, kiapu, transfer factor